2005
DOI: 10.1007/s10750-004-4876-1
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic vegetation and largemouth bass population responses to water-level variations in Lake Okeechobee, Florida (USA)

Abstract: A five-year study examined the responses of submerged aquatic vegetation (SAV), emergent vegetation, and largemouth bass (Micropterus salmoides) to variations in water level in a large lake in Florida, USA. SAV was assessed using a combined transect survey/spatial mapping approach, emergent vegetation was quantified with aerial photography and GIS, and bass were surveyed by electro-shocking. During the period leading up to this study (1995)(1996)(1997)(1998)(1999), water levels were high in the lake, and the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…Aquatic vegetation in Florida's shallow lakes is often the only structure or habitat available for fish populations (Havens et al 2005) and is one of the few factors impacting fish populations that can be effectively managed. The…”
Section: Managing Fish For the Benefit Of Peoplementioning
confidence: 99%
“…Aquatic vegetation in Florida's shallow lakes is often the only structure or habitat available for fish populations (Havens et al 2005) and is one of the few factors impacting fish populations that can be effectively managed. The…”
Section: Managing Fish For the Benefit Of Peoplementioning
confidence: 99%
“…In shallow eutrophic lakes a particularly important abiotic factor is water depth, because a change in depth of just one meter may translate into a large relative change in lake volume and substantially increased area that can be colonized by vascular plants and benthic algae (Havens et al, 2004). Increased coverage by plants can have substantial effects on recruitment of fish (Havens et al, 2005), biomass and composition of phytoplankton (Moss et al, 1997) and structure of the zooplankton (Schriver et al, 1995;Stansfield et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies documented that in response to the 2 year period (2000)(2001) of lowered water levels in Lake Okeechobee, the spatial extent of submerged aquatic plants increased from less than 150 ha in 1999 to over 15,000 ha in 2000, with a large spatial extent of plants persisting through 2004 (Havens et al, 2005). This response of the plants occurred due to reduced water depths, increased underwater irradiance, and oxidation of a layer of organic detritus in areas that became dry and then re-flooded, which allowed plants to germinate from oospores and seeds in the sediments (Havens, 2003;Havens et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, the degradation of aquatic vegetation has often been explained by increased nutrient loads (Scheffer and Carpenter, 2003;Tracy et al, 2003), and little attention was paid to hydrological alterations such as WLF in lakes (Van Geest et al, 2007). WLF can trigger regime shift between clear and turbid stable states in lakes, as low water level promotes the establishment of macrophytes by increasing light availability (Havens et al, 2005). Water level regulation is also regarded as an effective measure for aquatic vegetation restoration in lakes (Coops et al, 2004;Havens et al, 2004Havens et al, , 2005Li et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…WLF can trigger regime shift between clear and turbid stable states in lakes, as low water level promotes the establishment of macrophytes by increasing light availability (Havens et al, 2005). Water level regulation is also regarded as an effective measure for aquatic vegetation restoration in lakes (Coops et al, 2004;Havens et al, 2004Havens et al, , 2005Li et al, 2008). However, some studies still showed that extremely low or high water level is unfavorable to the growth of aquatic vegetation (Coops et al, 2003;O'Farrell et al, 2011) important to understand such requirements for a successful water level regulation with regard to aquatic vegetation restoration.…”
Section: Introductionmentioning
confidence: 99%